Expressão heteróloga, purificação e caracterização de proteínas transmembrana de Mycoplasma hyopneumoniae - Marchioro, Silvana Beutinger (2008)
Mycoplasma hyopneumoniae is the etiological agent of swine enzootic pneumonia (EP), one the most common respiratory diseases of pigs worldwide. The disease is characterized by retarded growth rate in animals of mid-finishing to slaughter age, causing significant economic losses to swine production. Vaccination is the most cost-effective strategy for the control of this disease. However, the vaccines against the disease available on the market have a high production cost and only offer partial protection, not preventing the establishment from infection and the presence of pigs carriers. This issue highlights the need for the use of new strategies aiming at circumventing this problem. The recombinant DNA technology is an important tool for the development of vaccines. The publication of the sequence of three genomes of M. hyopneumoniae, two pathogenic strains (232 and 7448) and a non-pathogenic (J) is helping the researches, and accelerating the process of identification of new antigenic proteins. From the sequence data and proteomic analysis, it was possible to identify coding sequences (CDS) of transmembrane proteins. These antigens were cloned and expressed using E. coli as an expression system. A total of seven recombinant proteins were purified and evaluated regarding immunogenicity in mice and antigenicity with sera from animals with EP. All the antigens evaluated were able to induce a significant immune response in mice. The evaluation of antigenicity properties revealed the proteins reacted with sera from pigs infected with M. hyopneumoniae. The recombinant proteins evaluated in this study may be of value to use in the development of vaccines and tests for immunodiagnosis of swine enzootic pneumonia.